Tripled fixed points theorems for (φ, ψ)-contractive operators on partially ordered metric spaces without mixed monotone - Phakdi Charoensawan (2018)
In this paper, we prove tripled fixed point theorem for nonlinear (φ, ψ)-contractive on partially ordered complete metric spaces without mixed monotone. We also prove the uniqueness of tripled fixed point of such mappings. Further, we extend the recent results of the tripled fixed point theorem of the given mapping with mixed monotone in partially orderd metric spaces. © 2013 Phakdi Charoensawan.